The Effect of Manipulated Prenatal Conditions on Growth, Survival, and Reproduction Throughout the Complete Life Course of a Precocial Bird - Vedder, Oscar; Bichet, Coraline; Tschirren, Barbara (Frontiers in Ecology and Evolution, 2022)
The quality of the environment individuals experience during development is commonly regarded as very influential on performance in later life. However, studies that have experimentally manipulated the early-life environment and subsequently measured individual performance in all components of fitness over the complete life course are scarce. In this study, we incubated fertile eggs of Japanese quail (Coturnix japonica) at substandard and standard incubation temperature, and monitored growth, survival, and reproduction throughout the complete life course. While embryonic development was slower and hatching success tended to be lower under substandard incubation temperature, the prenatal treatment had no effect on post-hatching growth, survival to sexual maturity, or age at first reproduction. In adulthood, body mass and investment in individual egg mass peaked at middle age, irrespective of the prenatal treatment. Individual reproduction rate declined soon after its onset, and was higher in females that lived longer. Yet, reproduction, and its senescence, were independent of the prenatal treatment. Similarly, adult survival over the complete lifespan was not affected. Hence, we did not find evidence for effects on performance beyond the developmental period that was manipulated. Our results suggest that effects of unfavorable developmental conditions on individual performance later in life could be negligible in some circumstances.